Topology Management of a Swarm of Unmanned Aerial Vehicles - Trotsyuk , Denys; Lesohorskyi , Kyrylo (Electronics and Control Systems, 2026)
The article is devoted to the problem of controlling the topology of a swarm of unmanned aerial vehicles (UAVs). The primary objective of swarm operation is maintaining a dynamic topology, i.e., stable information exchange and structural consistency between swarm elements in a constantly changing environment. It is shown that existing approaches rely on a global navigation satellite system (GPS) for UAV positioning, such as the Global Positioning System (GPS). This approach is unacceptable, as UAVs can suddenly experience loss of GPS signals while performing their missions, potentially resulting in a lack of location information. To support functionality, including the use of geographic routing protocols, maintaining connectivity in dynamic network conditions, and adapting to topological changes in the UAV swarm, this paper utilizes virtual coordinates. This paper develops a virtual coordinate system that forms the basis of the proposed method for UAV swarm topology management. This eliminates the need for global coordinates, a centralized controller, motion model coordination, and pre-calibration of the swarm formation. The system operates solely based on local distance measurements to neighbors, making it universal, scalable, and resilient to the loss of individual UAVs. Algorithms for merging and separating swarms based on the virtual coordinate system have been developed.